Tantangan Masa Pandemi Covid-19 terhadap Pembelajaran Sejarah di SMA Negeri 16 Medan - Ahmad Arif Budiman Nasution; Ahmad Fakhri Hutauruk; Andres M. Ginting (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This research is based on the findings of problems in historical learning conducted by blended learning in class XII at SMA Negeri 16 Medan during the Covid-19 pandemic. This research also aims to describe the challenges of teaching and learning through blended learning during historical learning in class XII at SMA Negeri 16 Medan. This type of research is qualitative research through a descriptive approach. The results of the study illustrate the challenges experienced by educators and learners. The challenges of educators are teachers lacking knowledge in blended learning, difficulty in providing assessments on blended learning, ineffective learning time, educators' ability to use gadgets, limited facilities and infrastructure, while the problems felt by students are difficulty in adjusting, lack of interest in learners when learning blended learning, learners' learning achievements are low, some learners cannot afford internet packages and have difficulty in accessing the internet network.